2009
DOI: 10.1243/14644207jmda200
|View full text |Cite
|
Sign up to set email alerts
|

Development of advanced textile materials: Natural fibre composites, anti-microbial, and flame-retardant fabrics

Abstract: The current trend in textiles is to move away from traditional uses and seek for increased complexity and ‘intelligence’ in terms of applications, so as to include them in the group of advanced materials, along with metal, ceramics, and polymers. Intensive research is in progress, following a multi-directed scheme where two key sectors can be distinguished: textiles structures and functionality. Representative examples of these two approaches are herein discussed regarding their applications, potentials, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
0
16
0
2
Order By: Relevance
“…This disruption is shown in Figure 5 at 70 C and is almost complete at 80 C. The smaller granules have less swelling and more stability, as shown in the thermal stability analysis. The average from other works [11][12][13][14][15][16][17][18] shows that the required enthalpy is close to 15 J.g À1 , and this behavior is linked to the degree of crystallinity and stability of the new structure formed by the gum.…”
Section: Ftirmentioning
confidence: 84%
See 1 more Smart Citation
“…This disruption is shown in Figure 5 at 70 C and is almost complete at 80 C. The smaller granules have less swelling and more stability, as shown in the thermal stability analysis. The average from other works [11][12][13][14][15][16][17][18] shows that the required enthalpy is close to 15 J.g À1 , and this behavior is linked to the degree of crystallinity and stability of the new structure formed by the gum.…”
Section: Ftirmentioning
confidence: 84%
“…[10][11][12][13][14][15][16][17] After 60 C, the granules swell and tend to maintain granular geometry. Some authors have observed gelatinization at 64 C. 17 However, the granular integrity destabilizes at 70 C due free movement of the internal structure. This disruption is shown in Figure 5 at 70 C and is almost complete at 80 C. The smaller granules have less swelling and more stability, as shown in the thermal stability analysis.…”
Section: Ftirmentioning
confidence: 99%
“…The development of microorganisms on textiles, particularly natural fibers-based textiles, could be talked about as far as huge responsive surface area alongside accessibility of appropriate conditions for developing i.e. moisture, oxygen, temperature and nutrients 29 . The development of microorganism has negative impacts on textiles as well as on the wearer (in case of clothes), since it brings about biodegradation of textile materials alongside their scattering health risk.…”
Section: Necessity Of Antibacterial Finishmentioning
confidence: 99%
“…The growth of microorganism on fabric has negative effects not only on the fabrics but also on the wearer, since it results in biodegradation of fabric materials along with their dissemination as a health risk [32]. An effective antibacterial finish should be quick acting, able to kill or stop the growth of microorganisms, durable to wash or dry cleaning, compatible with other finishing ingredients, environmental friendly, high quality but low cost, easy to apply and low toxicity [33].…”
Section: Antibacterialmentioning
confidence: 99%